The relationship between self-stigma and depression among people with schizophrenia-spectrum disorders: A longitudinal study. (May 2019) - Pellet, Joanie; Golay, Philippe; Nguyen, Alexandra; Suter, Caroline; Ismailaj, Alban; Bonsack, Charles; Favrod, Jérôme
Highlights: This study examined the relationship between self-stigma and depression in people with schizophrenia. Self-stigma was strongly associated with depression over time. Feeling discriminated against and having difficulties considering the positive aspects of the illness could predict and partially contribute to worsened depressive symptoms. Abstract: Harmful consequences of self-stigma in schizophrenia are well established in the literature, but its relationship with symptomatology remains unclear. Self-stigma describes the process by which some patients eventually accept, adhere to and apply to themselves the stereotypes associated with schizophrenia. This study aims to describe self-stigma experienced by people with schizophrenia in French-speaking Switzerland and to examine the relationship between self-stigma and depression. This was a longitudinal study including 80 participants. Correlation and regression analyses were used to examine the relationship between self-stigma and depression over three points of time. Correlations between Stigma Scale subdimensions and sociodemographic variables indicated that age and duration of illness were associated with the discrimination subscale. Self-stigma was strongly correlated with depression over time, whereby higher scores of self-stigma were associated with higher depression. More precisely, the more the patient felt discriminated against and the less he or she perceived the positive aspects of his or her illness, the greater the symptoms of depression. This study highlights the severity of self-stigma endorsed by people with schizophrenia in French-speaking Switzerland. The results provide new knowledge about self-stigma and its potential impact on depressive symptoms. Implementation of self-stigma assessment in clinical practice will allow distinctions to be made between the impact of self-stigma and the consequences of schizophrenia to recommend appropriate intervention.